Prognostic impact of coronary microvascular dysfunction assessed by AMR in acute coronary syndrome patients with chronic kidney disease - Guo, Ziyu; Li, Yike; Chen, Qiang; Zheng, Jingang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAngiography-derived microcirculatory resistance (AMR) is proposed as a novel, pressure- temperature-wire-free and less-invasive method to evaluate coronary microvascular dysfunction (CMD). This study aims to examine the prognostic role of CMD assessed by AMR in predicting adverse events in acute coronary syndrome (ACS) patients with chronic kidney disease (CKD).MethodsThis retrospective cohort study included ACS with CKD patients in the China-Japan Friendship Hospital from January 2016 to November 2022. The patients were divided into CMD and non-CMD groups based on AMR values of less than or greater than 250 mmHg*s/m.ResultsA total of 345 eligible patients were included in this study. During a median follow-up of 23.0 months, higher prevalence rate of MACEs (28.3% vs. 15.1%, P = 0.003) and death (20.2% vs. 4.1%, P = 0.001) were observed in the CMD group. In multivariate Cox regression analysis, patients in the group of CMD had a 1.843 times higher hazard ratio (HR) for developing MACEs (HR: 1.843, 95% CI: 1.071–3.174, P = 0.027) and 5.325 times higher HR for developing death (HR: 5.325, 95% CI: 1.979–14.327, P < 0.001) for every 10 mmHg*s/m increment in AMR. The incorporation of AMR improved the predictive accuracy of the GRACE score for MACEs and death.ConclusionThis study indicates that the AMR is significantly related to poor prognosis among patients with ACS and CKD. Furthermore, AMR could improve the predictive power of the GRACE risk score. These results indicated that AMR may serve as a valuable clinical tool for classification, risk stratification or therapy individualization in these patients.